Big book of what? - Nichols, Catherine (Time for Kids Books, 2012)
"Provides answers to a diverse collection of over eight hundred commonly asked factual questions, covering such areas as animals, space, the human body, food, survival, mysteries, and inventions."
"801 facts kids want to know"--Z obálky
Terminologický slovník
Obsahuje rejstřík
Keywords: všeobecnosti a zajímavosti; kuriozity, rekordy a zajímavosti; děti a mládež; facts and features; curiosities, records and wonders; children and youth; publikace pro mládež; juvenile literature